Dehydroepiandrosterone as an adjunct to gonadotropins in infertile Indian women with premature ovarian aging: A pilot study - Nisha Malik; Alka Kriplani; Nutan Agarwal; Neerja Bhatla; Garima Kachhawa; Raj Kumar Yadav (Wolters Kluwer Medknow Publications, 2015)
BACKGROUND: Dehydroepiandrosterone (DHEA) supplementation is a relatively recent development that augments ovarian responsiveness in patients with poor ovarian reserve and premature ovarian aging (POA). AIMS: To evaluate the efficacy of DHEA supplementation prior to gonadotropins for ovulation induction in women with POA. DESIGN: Prospective randomized controlled study. METHODS: Fifty infertile women with POA were randomized into two groups of 25 each. Group 1 received tablet DHEA 25 mg while group 2 received placebo thrice daily for 6 months. After 3 months, gonadotropin induction with intrauterine insemination was done. STATISTICAL ANALYSIS: Groups were compared using t-test and Mann-Whitney U-test as appropriate. Pre- and post-parameters were compared using t-test -paired and Wilcoxon signed-rank tests as appropriate. RESULTS: Of 50 patients, 62% (31/50) presented with primary and 38% (19/50) with secondary infertility. The mean age was 32.1 ± 4.7 years. Serum antimullerian hormone levels (1.5 ± 0.6-1.9 ± 0.4 ng/ml vs. 1.4 ± 0.5-1.5 ± 0.6 ng/ml) and antral follicle count (3.2 ± 1.0-9.3 ± 3.1 vs. 3.3 ± 1.1-3.4 ± 1.4) improved significantly in DHEA group after 3 months. Serum follicular stimulating hormone and estradiol levels though showed significant intra-group improvement (16.9 ± 5.5 mIU/ml to 14.7 ± 6.2 mIU/ml and 86.6 ± 57.5 pg/ml to 105.6 ± 54.3 pg/ml, respectively) with DHEA, the inter group difference was not significant. Ovulation increased from 48% to 86.3% in DHEA group versus 44-66% in placebo group. Six women (24%) conceived after DHEA in comparison to none in the placebo group. CONCLUSIONS: DHEA supplementation may have a beneficial role as an adjunct to gonadotropins in the treatment of infertility with POA, but further evidence is required.